Special effects : a look behind the scenes at tricks of the movie trade - Clise, Rick (Viking Kestrel ; Viking Penguin, 1986)
Explains how special effects are created in films to give the illusion of people on fire, spaceships moving through space, hideous monsters, and other effects.